THERMOELECTRIC SEMICONDUCTOR DEVICES FOR THERMAL STABILISATION OF REA POWERFUL TRANSISTORS - T. A. Ismailov; A. R. Shakhmaeva; A. M. Ibragimova (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim. The aim of the study is to analyse the problem of heat dissipation in high-power transistors and develop devices for their thermal stabilisation when used in electronic equipment. Method. A method is proposed for testing power transistors using a device to to ensure thermal stabilisation in the stating volume by means of a two-position temperature controller along with a model for the use of these components in electronic devices. The proposed devices support high thermal stabilisation accuracy of power transistors in a radioelectronic device system allowing temperature to be maintained at a given level with high accuracy by means of a thermoelectric battery. Results. Device designs were developed for increasing the accuracy of thermal stabilisation of power transistors with high efficiency, low energy consumption and small size. Conclusion. Based on the results of experimental studies, optimal designs for devices for the thermostabilisation of radioelectronic device components that dissipate significant power during their operation are presented. The devices can be used to increase the accuracy of thermal stabilisation of the radioelectronic device element by means of a working substance whose melting point coincides with its thermal stabilisation temperature. The developed devices have the following functions: the thermoelectric battery sections of the thermoelectric battery will be sequentially disconnected depending on the electrical signals from the temperature sensors to which the solid phase of the working substance has moved. The battery of the thermoelectric module (TEM) removes excess heat from the heat-stabilising substance while maintaining the required temperature of the radioelectronic device element. Excess heat from the heat-generating junctions of the TEM battery is removed by the heat exchanger. During melting of the working substance, the temperature of the thin-walled metal container – and, accordingly, the temperature of the CEA element – can be maintained at a constant value equal to the melting temperature of the working substance.